Interstitial Hypertension Suppresses Escape of Human Breast Tumor Cells Via Convection of Interstitial Fluid - Tien, Joe (Cell Mol Bioeng, 2020)
INTRODUCTION: Interstitial hypertension, a rise in interstitial fluid pressure, is a common feature of many solid tumors as they progress to an invasive state. It is currently unclear whether this elevated pressure alters the probability that tumor cells eventually escape into a neighboring blood or lymphatic vessel. METHODS: In this study, we analyze the escape of MDA-MB-231 human breast tumor cells from a ~3-mm-long preformed aggregate into a 120-μm-diameter empty cavity in a micromolded type I collagen gel. The “micro-tumors” were located within ~300 μm of one or two cavities. Pressures of ~0.65 cm H(2)O were applied only to the tumor (“interstitial hypertension”) or to its adjacent cavity. RESULTS: This work shows that interstitial hypertension suppresses escape into the adjacent cavity, but not because tumor cells respond directly to the pressure profile. Instead, hypertension alters the chemical microenvironment at the tumor margin to one that hampers escape. Administration of tumor interstitial fluid phenocopies the effects of hypertension. CONCLUSIONS: This work uncovers a link between tumor pressure, interstitial flow, and tumor cell escape in MDA-MB-231 cells, and suggests that interstitial hypertension serves to hinder further progression to metastatic escape. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12195-020-00661-w) contains supplementary material, which is available to authorized users.